A single base deletion in the 5' noncoding region of Theiler's virus attenuates neurovirulence. - Pritchard, A E (1992)
Viral chimeras have been constructed through in vitro manipulations of the infectious cDNA clones of two prototypes of Theiler's murine encephalomyelitis virus: (i) the virulent GDVII strain and (ii) the less virulent BeAn and VL strains. Previous studies have suggested that the phenotypic differences in virulence between the BeAn and GDVII strains map to both the 5' noncoding and the coat protein regions of these viral genomes. It is shown here that attenuation mapped to the 5' noncoding region is due, at least in part, to an inadvertent deletion resulting from a cloning artifact of one C nucleotide out of four between positions 876 and 879 in the BeAn sequences. The in vitro growth characteristics in BHK-21 cells, however, do not reflect the large differences in neurovirulence between chimeras that are identical except for the deleted C. Another chimera with a mutation at position 877 and a deletion at 976 is also attenuated. The wild-type sequences from the less virulent strains BeAn and VL between nucleotides 1 and 933, in an otherwise GDVII chimera, do not attenuate virulence. Sequences of the 500 nucleotides of the 5' noncoding region proximal to the translation initiation codon were obtained for nine additional Theiler's virus strains. The attenuating deletions are discussed in the context of these sequences and the proposed secondary structures for the 5' noncoding region.